Porous stamp-based reagent patterning for lateral flow immunoassays. Issue 18 (2nd May 2017) - Imdieke, Jessalyn; Fu, Elain
Abstract : We present a novel method of stamping antibody patterns onto nitrocellulose for lateral flow assays. Abstract : The lateral flow immunoassay (LFA) is the most common bioassay format in low-resource settings around the world. The ability to reproducibly create uniform protein patterns on porous substrates is a critical requirement for high performance LFAs. Common methods for patterning capture reagents during the LFA fabrication process rely on expensive, sophisticated liquid dispensing instruments that cost upwards of tens of thousands of US dollars and require substantial operator training. In the current report, we describe a simple method of patterning antibody onto nitrocellulose substrates using a porous material stamp. The method reproducibly produces uniform mm-scale patterns with less than ∼10% coefficient of variation in the average signal within the plateau region across replicate patterns.